Cyclic-AMP-dependent phosphorylation of glicentin. Issue 6 (June 1984) - Conlon, J. M.; Thim, L.; Moody, A. J.; Söling, H. D.
Abstract : Highly purified glicentin, a 69-amino-acid-residue peptide isolated from porcine intestine that contains the full sequence of glucagon and is probably biosynthetically related to glucagon, is a substrate for cyclic-AMP-dependent protein kinase in a cell-free system, Glicentin-related pancreatic peptide (residues 1–30 of glicentin) and glucagon were not phosphorylated under the same reaction conditions. It is postulated that the serine residue at position 34 of glicentin (position 2 of glucagon), that is part of the sequence Lys.Arg. His.Ser., is the probable site of phosphorylation.